Evaluation of Childhood COVID-19 Cases: A Retrospective Analysis - Akoğlu, Handan A.; Bulut, Muhammet; Alemdar, Dilek K.; Aslan, Serdar; Çelikkalkan, Kıvanç; Tursun, Serkan; Tekin, Emine; Baba, Hatice; Takır, Selçuk (Journal of Pediatric Infectious Diseases, 2021)
Objective This study aims to evaluate the demographic, epidemiological, and clinical features of novel coronavirus disease 2019 (COVID-19) cases aged between 0 and 18 years.Methods The demographic characteristics of the patients, admission symptoms, contact and travel histories, clinical onset duration, symptoms, treatments, laboratory findings, radiological images, and polymerase chain reaction (PCR) negation times were evaluated in a retrospective manner. Thirty-eight children (19 boys and 19 girls) were included in the study.Results The mean age of the patients was 10.36 ± 5.59 years. The average admission times of the patients after the onset of the symptoms was determined as 1.84 ± 2.02 days. Thirteen (34.2%) patients were observed as asymptomatic. The most common identified symptoms were fever, cough, and fatigue (55.2, 34.2, and 13.2%, respectively). Febrile convulsions, myalgia, dizziness, and diarrhea were the least common symptoms. Also, 25-hydroxyvitamin D3 (vitamin D3) levels were low and aspartate aminotransferase (AST) values were higher in the moderate group than the mild group and the relationships were statistically significant (p = 0.044and 0.027). Ferritin levels of the patients with ground glass opacity (GGO) were found statistically and significantly higher than the patients without GGO (p = 0,031). There was more than one lobe and segment involvement in five patients, the average number of affected lobes and segments was 3.8 and 8.8, respectively. High-resolution computed tomography of the 24 patients showed that; GGO in five (20.8%), consolidation + GGO (mixed) in three (12.5%), consolidation (alone) in one, subpleural linear opacities in three (12.5%), and pavement stone opacities in one (4.2%) patient. COVID-19, which is seen less frequently in children, may pose a risk in infants and young children.Conclusion Especially high ferritin levels may present with lung involvement and low vitamin D levels may worsen the aggravation of the lung involvement. There is a great need for further research on this subject.
Keywords: children; COVID-19; ferritin; vitamin D